The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/cm031081b
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Cyclopentanol:  Crystallographic Characterization of the Ordered and Disordered Phases

Abstract: The polymorphism of cyclopentanol (C5H10O) has been further investigated by X-ray powder diffraction experiments and it has been found to agree with the most recent thermodynamic study [J. Chem. Thermodyn. 1995, 27, 953]. In addition to the previously reported orientationally disordered hexagonal phases I and II, the lattice symmetry of the low-temperature ordered phases III and IV have been determined by means of pattern-matching analyses both as monoclinic with Z = 24 (Cc and C2/c, respectively). The pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…In this respect it is worth pointing out that the increase of the number of conformers within the asymmetric unit in a crystal makes it more difficult to find the thermodynamic path for energy minimization of the system as the temperature is lowered toward the ordered crystal ground state. 70,71 As far as the ordered phase II of C 6 CN is concerned, the contribution of the umklapp process is much larger than those for the orientationally ordered phases of C 6 OH. Because the umklapp process is the anharmonic phonon-phonon scattering process dominant for thermal resistivity providing the T −1 "pure" contribution, it can be concluded that this process is responsible for the low values of the thermal conductivity of C 6 CN beyond the phonon maximum if compared to values of the orientationally ordered phases of C 6 OH.…”
Section: B Orientationally Ordered Phasesmentioning
confidence: 99%
“…In this respect it is worth pointing out that the increase of the number of conformers within the asymmetric unit in a crystal makes it more difficult to find the thermodynamic path for energy minimization of the system as the temperature is lowered toward the ordered crystal ground state. 70,71 As far as the ordered phase II of C 6 CN is concerned, the contribution of the umklapp process is much larger than those for the orientationally ordered phases of C 6 OH. Because the umklapp process is the anharmonic phonon-phonon scattering process dominant for thermal resistivity providing the T −1 "pure" contribution, it can be concluded that this process is responsible for the low values of the thermal conductivity of C 6 CN beyond the phonon maximum if compared to values of the orientationally ordered phases of C 6 OH.…”
Section: B Orientationally Ordered Phasesmentioning
confidence: 99%
“…The molecules retain the same position in the hexagonal lattice, with different restricted rotations. [3] Phases III and IV have been confirmed as the monoclinic structure with space group C2/c and Cc, respectively, with a slight difference in the orientation of the molecule, resulting in the similar Raman spectrum. [3] Above 1.5 GPa, cyclopentanol crystallizes in the monoclinic P2 1 /c space group.…”
Section: Resultsmentioning
confidence: 82%
“…[3] Phases III and IV have been confirmed as the monoclinic structure with space group C2/c and Cc, respectively, with a slight difference in the orientation of the molecule, resulting in the similar Raman spectrum. [3] Above 1.5 GPa, cyclopentanol crystallizes in the monoclinic P2 1 /c space group. [11] However, it is observed that the Raman spectra of the crystalline state (phase III and IV) at lower temperature are different from that of the high pressure phase V. The peak splitting can be observed in the range of 800-950 cm −1 under high pressure, while it does not appear at the lower temperature.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, the existence of the OeH group gives rise to a hydrogenbonding interaction, which certainly contributes to the stabilization of a crystal structure [14]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%